2017
DOI: 10.3233/jad-160758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Risperidone and Galantamine Treatment on Alzheimer’s Disease Biomarker Levels in Cerebrospinal Fluid

Abstract: Background Treatment for neuropsychiatric symptoms (NPS) in dementia is insufficient. Antipsychotics and acetylcholinesterase inhibitors are used generating symptomatic improvements in behaviour and cognition, but few studies have investigated their effect on Alzheimer biomarkers in cerebrospinal fluid (CSF). Aim This is a secondary analysis based on an earlier clinical trial comparing the treatment effects on NPS. The aim of this study was to examine whether treatment with risperidone and galantamine affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…These inhibitory potentials, even far from that of the reference compound donepezil (6.7 nM) versus AChE [ 38 ], are close to those previously published for galanthamine (2.2 µg/mL and 11.7 µg/mL) or other plant extracts [ 4 , 39 , 40 ]. Interestingly, in spite of its moderate inhibitory potential, galanthamine is a typical drug used for the treatment of Alzheimer's disease [ 41 ], validating our efforts to identify new potential inhibitory compounds. Niphogeton dissecta essential oil exhibited selectivity for the inhibition of BChE, this property being particularly interesting in the treatment of Alzheimer's disease [ 40 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…These inhibitory potentials, even far from that of the reference compound donepezil (6.7 nM) versus AChE [ 38 ], are close to those previously published for galanthamine (2.2 µg/mL and 11.7 µg/mL) or other plant extracts [ 4 , 39 , 40 ]. Interestingly, in spite of its moderate inhibitory potential, galanthamine is a typical drug used for the treatment of Alzheimer's disease [ 41 ], validating our efforts to identify new potential inhibitory compounds. Niphogeton dissecta essential oil exhibited selectivity for the inhibition of BChE, this property being particularly interesting in the treatment of Alzheimer's disease [ 40 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bloniecki et al. found that in a cohort of subjects with AD and NPS agitation measured with the Cohen‐Mansfield Agitation Inventory (CMAI) correlated with total‐tau (r = 0.36, P = .04) and phosphorylated‐tau r = 0.35, P = .05) in AD patients, indicating that tau‐mediated pathology including neurofibrillary tangles and the disease intensity might be associated with agitation in AD 156,157 . In their systematic review of CSF correlates of NPS in AD and aMCI, Showraki et al.…”
Section: Biomarkers Of Npsmentioning
confidence: 99%
“…Side effects include nausea, vomiting, loss of appetite and increased frequency of bowel movements. Among three cholinesterase inhibitors that are commonly prescribed, Aricept is approved to treat all stages of AD whereas Exelon and Razadyne are approved to treat mild to moderate AD [ 134 , 135 , 136 ]. Memantine regulates the activity of glutamate, which is a chemical involved in information processing, storage and retrieval [ 137 ].…”
Section: Introductionmentioning
confidence: 99%